Project Management in Development Cooperation. Non-Governmental Organizations (2015)
This article analyzes the adoption of project management practices in development cooperation NGOs and their influence on project performance. This paper illustrates the impact in the implementation of methodologies, techniques and tools on outcomes, measured by success criteria of several projects recently implemented. Information from the project managers of the organizations was collected, and complemented by a literature review. We analyzed the correlation among the variables that determine the adoption of a project, and the criteria that determine its success. The positive effect of project management adoption in the performance of cooperation projects is demonstrated, in spite of the low use of methodologies, techniques and tools within the sector. The article shows the importance of project management in cooperation and aid projects, with the purpose of increasing researchers' awareness about the field as applicable knowledge and about the benefits of its use in the sector. The paper shows that project management can improve project efficiency and accountability in other sectors.